Recalcitrant Incomplete Secukinumab Administration in a Psoriasis Patient - Gani Panjaitan, Joice Sonya; Suhartomi, Suhartomi (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Psoriasis is an immunologic-mediated disease affected by genetic factors that may affect the skin, joints, and cardiovascular system. Some biological agents have been developed and approved by FDA to treat psoriasis. One of these biological agents is Secukinumab, a fully human IgG1κ anti-interleukin-17A(IL-17A) monoclonal antibody. Case Presentation: A seventeen female teenager came to Dermatovenerology Clinic with scaly patches in the forehead and hairline around ten months ago with a history of repeat Corticoticosteroid, DMARDs, and biologic agent treatment. Dermatology examination showed erythema, induration, and desquamation in head and extremities with PASI score of 1.2. She was treated with initial and maintenance doses of Secukinumab Injection.Conclusion: It can be concluded that the recalcitrant administration of Secukinumab in Psoriasis patients may decrease the treatment response.